Self-quadplexing slot antenna for S and C-band applications - Padmini Nigam; Sandeep Sharma; Amrindra Pal; Arjuna Muduli (Computer Science and Information Technologies, 2022)
This paper demonstrates a novel kind of cavity-backed self-quadplexing slot antenna for the S and C-band applications. The proposed antenna consists of 4 distinct “U”-shaped slots of different lengths and produces the quad frequency band for wireless communication systems. These slots are excited through the separate and orthogonal placed microstrip feed lines of 50 Ω; generates four distinct operating bands at 3.2 GHz, 4.1 GHz, 5.8 GHz, and 7.2 GHz. Due to the perturbation of different U-shaped slots over the substrate integrated waveguide (SIW) cavity with defined positions, the high intrinsic port isolation value is better than 30.5 dB. Thus, the proposed unique antenna structure combines the four independent operating bands with minimum mutual coupling and negligible interference among input ports, which shows the self-quadplexing feature of the antenna. The proposed antenna also has the property of frequency tunability with uni-directional radiation pattern and gain of 5.8 dBi, 5.4 dBi, 4.01 dBi, and 3.47 dBi at corresponding operated frequency. The cross-polarization is 17.3 dB and the front-to-back ratio higher than 21.5 dB at all operating quad bands. There is a good agreement between simulated |S|-parameters results and equivalent circuit model results.